The effect of CuO on a Pt−Based catalyst for oxidation in a low-temperature fuel cell - Suphitsara Maturost (2020)
© 2020 Hydrogen Energy Publications LLC Electrocatalytic oxidation of methanol, ethanol, and formic acid has currently attracted research attention for low-temperature fuel cells. However, the efficiencies of these fuel cells mainly depend on the electrocatalytic activities of Pt-based anodic catalysts due to the problems of low kinetics for small organic molecule electro-oxidation. An anode catalyst can be developed by the addition of some metal oxides into a Pt-based catalyst, which can effectively promote the electro-oxidation of fuels based on small organic molecules. In this work, a nanocomposite catalyst consisting of multi-wall carbon nanotubes (CNTs), copper oxide (CuO) and Pt nanoparticles was synthesized and used to improve fuel cell oxidation. Due to its low cost and oxophilic character, the metal oxide can play a major role in the oxidation of CO. The synthesis of xPt−yCuO/CNT electrocatalysts was executed through two steps: supporting of CuO nanoparticles on CNTs by the alcothermal method followed by Pt loading onto the prepared CuO/CNT by chemical reduction. The as-prepared catalysts were physically characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Raman spectroscopy, and electrochemical measurements. The results demonstrate that CuO is well dispersed onto the CNTs and that this oxide can further interact with the active Pt present on the as-prepared catalyst composites. The activity of various xPt−yCuO/CNT electrocatalysts was determined by cyclic voltammetry (CV), where x and y are the mass ratios of Pt and CuO, respectively. The presence of CuO was found to significantly contribute to enhanced electroactivity towards oxidation reactions. The 1Pt–3CuO/CNT electrocatalyst is a capable catalyst for improving low-temperature fuel cell applications.